The golden triangle role of human resources in building of organizational Ambidexterity - Adel Kased. M. Al-Assadi; Hussam Ali Mhaibes; Ansam Ghazi Abbood (Eximia, 2024)
The main objective of this research is to determine the role of the Golden Triangle of Human Resources in building organizational ingenuity (as applied to the Ministry of Planning). The research also seeks to achieve a set of objectives, namely to determine and measure whether there are significant differences of statistical significance between the views of the sample vocabulary on the dimensions of the Golden Triangle of Human Resources and organizational ingenuity. A model of the study has been proposed that illustrates the dimensions of the human resources triangle and organizational ingenuity, as has the design of the search tool. The study was based on an analytical-descriptive approach and a comprehensive individual survey of the research sample. The tests to measure the authenticity and consistency of the research tool (resolution) were conducted and directed to a sample of managers working in the Ministry of Planning (Sector Service, Directorate of Regional and Local Development, and Investment Service). The sample was uniquely sized, with the total number of valid lists for statistical analysis (105) being 88% of the total sample size. The results of the statistical analysis indicated a positive statistically significant impact of the triangle dimensions of human resources in building organizational mastery in the ministry in question.